Non-Contrast Enhanced Magnetic Resonance Venography Using the Fast Imaging Employing Steady-State Acquisition (FIESTA) Pulse Sequence in Preoperative Evaluation of Liver Donors: Can it Replace CT Venography? - Huma Hussain; Muhammad Salman Rafique; Sana Kundi; Tahir Malik; Bushra Bilal; kayenat khan (Shalamar Medical & Dental College, Lahore, Pakistan, 2023)
Background: Liver transplantation has now become the preferred treatment for patients with liver failure. Pre-operative assessment of hepatic/portal vein anatomy of donors is necessary for which CT venography is most commonly used but it exposes the donors to huge radiation burden. To avoid this, non-contrast MR venography is the most preferred alternative for evaluation of veins. Objective: To determine diagnostic yield of magnetic resonance venography using Fast Imaging Employing Steady-State Acquisition (FIESTA) pulse sequence in comparison to computed tomography venography for the determination of portal/hepatic venous anatomy of potential liver donors. Methods: Retrospective study was conducted in which the venous phase CT scan and FIESTA (b-SSFP) sequence of 50 potential liver donors between 01-07-2021 and 30-11-2021 were reviewed. The hepatic and portal venous anatomy was reviewed. The assessment comprised the type of portal venous anatomy, the number of prominent tributaries from segment VIII and V of liver having diameter of 4mm or more emptying into the middle hepatic vein and the total number of accessory inferior right hepatic veins from segment VI and VII emptying into inferior vena cava (IVC). Results: With 100% sensitivity and specificity, the FIESTA sequence precisely identified the portal vein anatomy, total number of accessory inferior right hepatic veins, and the total number of 4 mm thick tributaries from segment V and VIII draining into middle hepatic vein Conclusion: We propose that magnetic resonance venography using FIESTA sequence can be used instead of CT venography to determine hepatic and portal vein anatomy of liver donors.